Body Mass Index and disordered eating behaviors: a cross-sectional study of a community sample participating in an obesity awareness campaign - Ramalho,Sofia (2018)
Introduction: Several behavioral and lifestyle factors, including disordered eating behaviors, interact in the development and maintenance of overweight and obesity in adults. Objectives: The present study aimed to describe the anthropometric, sociodemographic, and lifestyle characteristics, as well as the disordered eating behaviors of a community sample collected during an Obesity Awareness Campaign. Furthermore, the association between Body Mass Index, age, gender, food, beverages intake, and disordered eating behaviors is to be explored. Methodology: This sample was composed of 109 participants (59% women, aged 39.7 ± 15.5 years; Body Mass Index 24.8 ± 3.6) who agreed to participate in an Obesity Awareness Campaign promoted in a shopping mall in the north of Portugal. Body Mass Index and disordered eating behaviors (uncontrolled eating, emotional eating, and cognitive restriction) were the main measures evaluated. Results: Participants with obesity presented significantly more uncontrolled eating and emotional eating levels when compared to participants with overweight and normal Body Mass Index. No statistically significant differences were found between genders, age groups (18-28; 29-39; 40-50; 51-61; over 62 years) and disordered eating behaviors. Conclusions: The results seem to indicate a positive link between disordered eating behaviors (uncontrolled and emotional eating) with the intake of unhealthy food/beverages, which can consequently lead to increased caloric intake and difficulties in weight management. The present findings alert clinicians to the importance of assessing disordered eating behaviors in individuals with obesity, providing useful information to customize clinical recommendations and intervention strategies, mainly in regard to the associations between food/beverage consumption and disordered eating behaviors.